Implementación de la metodología Biogaval en la evaluación y prevención de riesgos biológicos ocupacionales en las actividades del personal de un laboratorio de análisis clínicos Arequipa – 2018” - Huacani Limachi, Evelyn Darleny (2019)
The development of work activities, the contemplation of some form, direct or indirect, the risks inherent to the work activity, the same that should be minimized, the means of the evaluations, the controls and the processes that diminish. Then, occupational safety has become an important activity for the well-being of people. The present research work, raised as its objective, the evaluation and implementation of a security program, is based on a methodology recognized as BIOGAVAL. This methodology allows to measure both the biological risk and the people who work in a clinical analysis laboratory, located in the city of Arequipa. The work, maintains a quantitative research design, with a descriptive level, and the regulation of qualification and registration of Researchers in Science and Technology of SINACYT is of applied type, as well as transversal. However, a total of 15 people.We worked with the total population of the laboratory, so no sampling of any kind was used, with a total of 15 people. The information of a questionnaire, which contained 10 items. Once the information was processed, it was concluded that 40% of the workers have experience in a clinical laboratory in a time parameter that ranges between 11 and 15 years. In the case of PPE, 47% always use them. For the case of the highest possible cause of risk, 47% indicated that it is exposure to punctures. 67% of the staff consider that the level of biological risk is high in the clinical laboratory service, while 54% of the personnel frequently meet the general biosafety norms. In addition, 47% consider that an adequate management of solid waste is frequently carried out. 60% of the personnel, refers that the training to the personnel, in subjects related to biological risk, is carried out in a frequency of "sometimes". For 40% of workers, hand washing, before and after handling a patient, develops on a frequency of "sometimes". 47% of the staff always re-hoof the needle after use. 53% of the staff has frequently suffered from an illness during their work in the clinical laboratory service. The most important biological agents were Hepatitis B virus (HBV), Hepatitis C virus (HCV) and (HIV), influenza, being a common virus. The Biogaval Method, determined that the hygienic measures adopted by the clinical laboratory are deficient since they only comply with 47% effectiveness, in terms of biological action level (NAB) and biological exposure limits (LEB), and the results exceed the permissible valuesof 12 and 17 respectively. With this method, the control measures that will be implemented in the clinical laboratory are determined.